La culture en tant que cultivation : vers une conception communicationnelle de la culture organisationnelle - Nicolas Bencherki; François Cooren; Boris H. J. M. Brummans; Chantal Benoit-Barné; Frédérik Matte (Communiquer)
Although organizational culture research is well established, surprisingly few researchers have studied how culture is a communicative accomplishment. By relying on the analysis of interviews, rather than interactions, many studies do not provide insight into how various actors produce and reproduce organizational culture in the practice of communication. This paper addresses this issue by adopting a ventriloquial perspective to show how culture can be viewed as a communicative process in which actors mobilize values, principles, documents, and so on that they position as guiding or animating their actions. Hence, this paper situates culture at the level of observable interactions and communicatively “concretizes” this concept.